Karakteristik kimia dan potensi antioksidan dari kombucha berbahan kulit batang faloak (Sterculia quadrifida R.Br) - Paulus Risan F. Lalong; Elok Zubaidah; Erryana Martati (Teknologi Pangan: Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2022)
Faloak (Sterculia quadrifida R.Br) stem bark tea is consumed as herbal drink by some people on Timor Island, East Nusa Tenggara. The potential and bioactive content of faloak stem bark can be increased by fermenting it into kombucha, considering that there has been no use of stem bark, especially faloak stem bark, as the main substrate in kombucha fermentation. This study aims to examine the effects of various concentrations of faloak stem bark tea (0,8, 1,2, 1,6, 2% (w/v)) on the chemical characteristics (pH, total acid, total phenol, total sugar) and the antioxidant potential of faloak stem bark kombucha during the fermentation process on Day 0 and Day 14. During 14 days of fermentation, it was found that the concentration of faloak stem bark tea, with the best concentration of 1.6% (w/v), had a significant effect on changes in chemical characteristics and antioxidant activity, namely pH 2.6, total acid 0.62%, total sugar 7.15% total phenol 467.92 mg/L GAE, total flavonoid 4135.14 mg/L QE, and antioxidant activity of 82.21%. Therefore, faloak stem bark tea has the potential to be used as a substrate in the making of kombucha with tea concentration of 1.6% (w/v) fermented for 14 days.